Annual Report on Exchange Arrangements and Exchange Restrictions 2016. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
The AREAER provides a description of the foreign exchange arrangements, exchange and trade systems, and capital controls of all IMF Member countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet